Haemosporidian Parasites in Domestic and Wild Birds - Essa, Isra’a M. (Journal La Lifesci, 2025)
This study aims to provide brief information about the role of haemosporidian parasites in birds and significant implications for avian health, population dynamics, and control efforts. Haemosporidian parasites, belonging to the phylum Apicomplexa, are a diverse group of protozoan organisms that infect a wide range of vertebrate hosts, including birds. These parasites have a complex life cycle, with both sexual and asexual stages, and are transmitted by blood-feeding insects such as mosquitoes, midges, and blackflies. The potential impact of these parasites include a wide range of health issues in infected birds, including anemia, decreased body condition, and reduced reproductive success. Additionally, the distribution of parasitic populations within individual hosts can lead to complex interactions between the host and its parasites, which can influence the overall population structure and dynamics of both the host and the parasite. The prevalence and genetic diversity of haemosporidian parasites can also vary depending on various factors, such as the migratory patterns of birds, availability of suitable vectors, and environmental conditions in different regions. In conclusion, haemosporidian parasites play a crucial role in the dynamics of bird populations, influencing their health, fitness, and population structure. Understanding the complex interactions between these parasites and their avian hosts is essential for developing effective strategies for the conservation and management of bird populations.